REVIEW STUDY OF SUSHRUTOKTA SHAV SAMRAKSHAN VIDHI IN THE MODERN PARAMETER - Kuldeep Kumar; Tiwari Namrata; Dwivedi Sushil (International Journal of Applied Ayurved Research, 2018)
Dissection is the base of practical knowledge of human anatomy for medical students and before the dissection; there is a need of preservation of dead body. In ancient era, Acharya Sushrut was the first physician who performed the dissection of human dead body. He explained the procedure of dead body preservation and method for dissection. He had explained the method at the time when touching a dead body was taboo in the society. For this procedure, Sushrut has used totally natural materials which are found anywhere easily. In modern era, the dead body preservation is done with the prepared solution of various chemicals. This process is called embalming.Some unsolved, doubtful and mysterious topics of Ayurvedic Rachana Sharir can easily understand, if we correlate them with the modern anatomy. Hence, it is very essential to compile and correlate the method of preservation and dissection given by Acharya Sushrut with the recent method of embalming. In this paper, we will discuss the Sushrutokta method of preservation and dissection of human dead body in detail along with the modern techniques.